CSR communication and international marketing: Insights from the COVID-19 pandemic - Farmaki, Anna; Hadjielias, Elias; Olya, Hossein; Taheri, Babak; Drotarova, Maria Hadjielia (My University, 2022)
Purpose: The purpose of this study is to analyze the corporate social responsibility (CSR) communication of the Fortune top-100 companies during the coronavirus disease 2019 (COVID-19) pandemic. Specifically, the authors examine the messages of international companies' CSR communication to customers during the pandemic, focusing particularly on the companies' posts on Twitter. In addition to identifying what international companies communicate, the authors determine the motives of companies' COVID-19-related CSR communication as well as how companies strategically approach CSR communication. Design/methodology/approach: Using Nvivo, the authors carried out content analysis of the COVID-19-related tweets of the Fortune top-100 companies using Twitter's ‘advanced search’ tool. The analysis included tweets posted between 1 February 2020 and September 2021, a period that represents the peak of the pandemic. Findings: Study findings indicate that COVID-19-related CSR responses of international companies are driven by commitment to organizational values, attainment of recognition for timely response to COVID-19, altruistic motives to combat COVID-19 and congruence with social movements that create expectations from customers to respond to the COVID-19 pandemic. Most companies adopt a response strategy to CSR communication, by informing customers of their COVID-19 responses in relation to several issues such as alterations in companies' processes and the impacts of the pandemic on health. Practical implications: The study suggests that the CSR practices of companies should be strategically embedded in organizations' international marketing plans and not remain just on-off responses to crises should marketing-related benefits be obtained. Several recommendations are made to strengthen companies' adoption of a proactive, engagement-oriented approach to CSR communication. Originality/value: The CSR communication of international companies during external crises has not been sufficiently studied in relation to international marketing, as most studies considered internal corporate crises. Focusing on an external crisis (COVID-19 pandemic) with global impacts, this study advances existing knowledge on international companies' CSR communication to their customers. Additionally, this study offers new insights on the role of integrated, coordinated and consistent CSR messages and strategies, which are targeted to the needs and expectations of domestic and international customers in response to COVID-19 pandemic.
Keywords: Content analysis; COVID-19 pandemic; Crises; CSR communication; International marketing; Twitter